1978
DOI: 10.1002/eji.1830081202
|View full text |Cite
|
Sign up to set email alerts
|

Selective participation of immunoglobulin V region and major histocompatibility complex products in antigen binding by T cells

Abstract: Antigen-binding inhibition studies using microscopic autoradiography were performed on T or B cell-enriched lymphocyte populations. Antibodies specific for the "framework" of immunoglobulin heavy or light chain variable domains (VH or VL), or anti-H-2 and anti-Ia antisera were used. T cell subclasses were separated with anti-Lyt antisera and complement. It was found that antigen-binding T cells of different subclasses can be inhibited selectively with only one of the two anti-V region antibodies. Antigen bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 24 publications
7
27
0
Order By: Relevance
“…In contrast, anti-Vx and anti-V, did not retain helper activity, and all of the activity appeared in the column effluent. These data are in agreement with a number of other results obtained with our anti-VH region reagents (24)(25)(26) or with anti-idiotypic antibodies (27)(28)(29).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, anti-Vx and anti-V, did not retain helper activity, and all of the activity appeared in the column effluent. These data are in agreement with a number of other results obtained with our anti-VH region reagents (24)(25)(26) or with anti-idiotypic antibodies (27)(28)(29).…”
Section: Resultssupporting
confidence: 93%
“…The reagents used in these experiments were extensively characterized by serological (21-23) as well as functional experiments. It has been shown that anti-Vn but not anti-VL inhibits antigen binding by Lyt-1 +,2-,3-normal lymphocytes (24); that anti-Vn but not anti-Vx inhibits streptococcal carbohydrate-specific helper cells (25), and also that anti-Vn but not anti-Vx or anti-V~ protects helper T cells from radioactive antigen "suicide" (26). Additional studies have shown that anti-Vn binds the Ig-receptor of hapten-specific T cells (30), that it interferes with the binding of membrane receptors by allostimulated T cells (31), and that it is present on the (32) and helper-factor-producing hybridomas (33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have demonstrated that IAC contains Ia antigens and that it is bound by helper T cells via receptors that share determinants with the "framework" of immunoglobulin VH (7,13,14). This was confirmed by the inhibition ofbinding in the presence of3 pug of anti-V11 and by the loss ofbinding activity in the IAC preparation after it was passed through an anti-IakSepharose column.…”
Section: Methodsmentioning
confidence: 68%
“…T cells which mediate delayed-type hypersensitivity (TDn) (16) and helper T cells (17) recognize antigen in association with I region-encoded determinants. Furthermore, Lonai and co-workers (18) had reported that antigen binding to Lyt-1 + cells was inhibited by anti-VH antiserum, whereas antigen binding to Lyt2+3 + ceils were inhibited by anti-VL specifically.…”
mentioning
confidence: 99%